Associations of Triglycerides/High-Density Lipoprotein Cholesterol Ratio With Insulin Resistance, Impaired Glucose Tolerance, and Diabetes in American Adults at Different Vitamin D3 Levels - Liu, Yuanyuan; Gong, Rongpeng; Luo, Gang; Li, Jinxia; Li, Qidan; Yang, Lixin; Wei, Xiaoxing (Frontiers in Endocrinology, 2022)
Abstract Background：Previous studies have shown that vitamin D3 (VD3) may be a protective factor for diabetes mellitus (DM), while triglycerides/high-density lipoprotein (TG/HDL) may be a risk factor for diabetes. However, no existing study has elucidated the interaction between TG/HDL and VD3. Therefore, this work aimed to investigate the relationships of TG/HDL with insulin resistance (IR), impaired glucose tolerance (IGT) and DM at different VD3 levels. Methods：Using the data from five NHANES cycles, a total of 2929 males and 3031 females were divided into 4 groups according to their VD3 levels. Logistics regression was performed to observe the associations of TG/HDL ratio with IR, IGT and DM in different groups. Results：The relationships of TG/HDL with IR, IGT and DM showed threshold effect, with the cut-off values of 1.094, 1.51 and 1.11, respectively. On both sides of the cut-off values, the correlation was first weakened and then enhanced with the increase in VD3 level. Conclusion：TG/HDL is a risk factor for IR, IGT and DM. Both too low and too high levels of VD3 can strengthen this association. Whereas keeping VD3 at a reasonable level helps to reduce the associations of TG/HDL with IR, IGT and DM.